Gene expression regulation by a stress-responsive transcription factor in rice seedlings - Williams, Seré, author; Reddy, A. S. N., advisor; Leach, Jan, committee member; Bush, Daniel, committee member (Colorado State University. Libraries, 2019)
Stress physiology is an inherently complex field. As plants cannot leave their environment when it becomes unfavorable, they have developed multiple mechanisms to cope with stresses. Many of these are unique to plants compared to mobile organisms. Plant stress physiology is of interest not only for this reason, but because the human population relies on agriculture for food. Additionally, our ecosystem relies on plants as primary producers as an integral component of life on earth. Plant stress physiology at the molecular level involves a symphony of signaling cascades that reshape cell physiology and communicate the stress signal to the whole plant and even nearby organisms. Over the last thirty years, enormous progress has been made to identify key genes, hormones, and signaling pathways that are involved in plant stress responses. To this end, we have yet to understand a cohesive picture of how plants respond to a combination of stresses. Given the variety of biotic stresses from bacteria, fungi, viruses, nematodes, and herbivores and their interaction with abiotic stresses including environmental extremes and resource availability, continued efforts are needed to understand the molecular nuances of plant stress responses. Not only are stresses variable and unique, plants have evolved to thrive in specific habitats, thereby developing unique strategies to cope with local environments. For example, rice grows well in flooded soils which would induce a stress-response in typical, non-aquatic organisms. Therefore, stress response will need to be decoded at the level of the organism. The goal of this work is to better elucidate stress response in rice. Specifically, I have looked at the influence of a transcription factor, SIGNAL RESPONSIVE 1 (OsSR1), that is regulated by Ca2+/CaM and known to be a dynamic regulator in a myriad of stresses in Arabidopsis. I have generated complemented lines of Ossr1 mutant and OsSR1 overexpressor transgenic rice lines. When compared with WT and mutant lines, these lines showed a range of OsSR1 expression. These lines will be of great help in deciphering the action of this transcription factor. Homozygous SR1 complemented and overexpressor lines along with WT and Ossr1 mutant will be used in future studies to better understand the action of SR1 in stress response in rice. Additionally, I performed a factorial global gene expression analysis using RNA-seq with WT and Ossr1 lines at the seedling stage in control and drought conditions, which will serve as a breeding ground for hypothesis generation and testing in future studies. Significant differentially expressed (DE) genes show down-regulation of genes encoding serine threonine-protein kinase receptor (SRK)-receptors, kinases, TCP family transcription factor, cytokinin-modifying enzyme and up-regulation of aquaporin, sucrose synthase, G-protein-related, and ferredoxin-nitrate reductase in the mutant when compared to WT. In response to polyethylene glycol (PEG)-induced drought stress, the mutant up-regulated transcription factors (homeobox [HOX]- containing TFs, WRKY, and DIVARICATA), signaling proteins (protein phosphatases), late embryogenesis abundant protein 1 (LEA1), nodulin-related genes, and senescence-associated gene 21 (SAG21), while down-regulating a CaM-dependent protein kinase, efflux transporters, peroxidases, aquaporins, and disease-related genes including Pathogenesis-related protein PRB1-2, disease resistance protein RPS2, and NB-ARC domain-containing protein. Lastly, significant DE genes in the WT illuminate how this important crop plant responds when exposed to PEG-induced drought. Drought induced the expression of MAPKKKs, ethylene-responsive transcription factors (ERFs), HOX TFs, as well as zinc-finger proteins and protein phosphatase 2Cs. In drought, WT down-regulated glycol-lipid transfer proteins, aquaporins, and salt stress-induced proteins. Gene ontology (GO) analysis of significant DE genes showed enrichment of GO terms related to membranes, oxidative stress, response to stimulus, and transcription regulation in both the WT and mutant when exposed to PEG. Future work will analyze the promoters of candidate genes for the OsSR1 DNA-binding motif (CG-1) to identify direct targets of OsSR1. Rice is the model organism for monocots and provides 15% of the calories consumed by humans. This study and other studies based on this work will help in elucidating the functions of this stress-responsive transcription factor, OsSR1, in this important crop plant.